Analysis of Physical and Chemical Properties of Void Water Post Coal Mining Relationship With Aquaculture - Henny Pagoray; Komsanah Sukarti; Andi Nikhlani; M. Ma’ruf (Bionature, 2023)
Identification of the quality of void water after coal mining needs to be carried out in order to utilize the void as a place for fish farming. Identification of water quality, in the form of physical and chemical water. Physical and chemical parameters can influence the survival of cultivated biota, so research needs to be carried out to identify both physical and chemical water parameters related to aquaculture. The research method involves taking and measuring water samples in both in situ and ex situ settings. Measurements were carried out at three (3) sampling points, sampling four times. The parameters under observation include temperature, TSS (Total Suspended Solids), pH, brightness, dissolved oxygen (O2), biological oxygen demand (BOD), chemical oxygen demand (COD), nitrate (NO3), nitrite (NO2), ammonia (NH3), and hydrogen sulfide (H2S). A descriptive analysis of water quality is conducted, and the results are compared against the quality standards outlined in the Provincial Regulations of East Kalimantan, specifically, Number 2 of 2011, which pertains to Water Quality Management and Water Pollution Control (APPENDIX V, Class III). The results of the water quality analysis physically show that the temperature is 29.5 –31oC brightness 135 – 285 Cm, TSS 13.75 – 27.5 mg/L, Chemical pH 7.42 – 7.68, O2 4.26 – 4.84 mg/L, BOD 0.64 – 1.84 mg/ L, COD 2.96 – 5.93 mg/L, NO3 0.026 – 0.049 mg/L, NO2 0.002 – 0.006 mg/L, NH3 0.01 – 0.13 mg/L and H2S 0 – 0.0087 mg/ L. Both the physical and chemical water quality parameters conform to the standards established in the East Kalimantan Province Regional Regulation Number 2 of 2011, which focuses on Water Quality Management and Water Pollution Control. As a result, the post-coal mining void water's condition, in both physical and chemical aspects, remains suitable for aquaculture.